فعالية استخدام وسائل التعليم على الإنترنت في تعليم اللغة العربية لدى طلاب الصف العاشر بالمدرسة الثانوية المهنية الحكومية ٧ تانجرانج - Nabila Zzahra Sabrina Putri Suwandi; Lukmanul Hakim (Prodi Pendidikan Bahasa Arab, Universitas Muhammadiyah Tangerang, 2022)
AbstractThe purpose of this study was to find out how the use of learning media in the 7th State Vocational High School Tangerang Regency, to find out what problems were encountered in the application of learning using learning media, and to determine the extent to which the effectiveness of the use of this learning media in learning Arabic for class students. X at the 7th State Vocational High School, Tangerang Regency.This type of research is descriptive with a qualitative approach. Collecting data using interviews, observation, and documentation methods. Test the validity of the data using data source triangulation techniques. The data analysis technique used by the researcher is data reduction, data presentation, and data verification.The results of this study indicate that learning to use online media in students' Arabic subjects is less effective. To increase the effectiveness of using online media in Arabic subjects, it is hoped that the school, teachers, and parents can work together in supervising and guiding the student learning process.Keywords: Effectiveness, Online Learning, Arabic Lessons.